FGF‐23 and cognitive performance in hemodialysis patients. Issue 1 (24th October 2013) - Drew, David A.; Tighiouart, Hocine; Scott, Tammy M.; Lou, Kristina V.; Fan, Li; Shaffi, Kamran; Weiner, Daniel E.; J. Sarnak, Mark
Abstract Although cognitive impairment is common in hemodialysis patients, the etiology of and risk factors for its development remain unclear. Fibroblast growth factor 23 (FGF‐23) levels are elevated in hemodialysis patients and are associated with increased mortality and left ventricular hypertrophy. Despite FGF‐23 being found within the brain, there are no prior studies assessing whether FGF‐23 levels are associated with cognitive performance. We measured FGF‐23 in 263 prevalent hemodialysis patients in whom comprehensive neurocognitive testing was also performed. The cross‐sectional association between patient characteristics and FGF‐23 levels was assessed. Principal factor analysis was used to derive two factors from cognitive test scores, representing memory and executive function, which carried a mean of 0 and a standard deviation of 1. Multivariable linear regression adjusting for age, sex, education status, and other relevant covariates was used to explore the relationship between FGF‐23 and each factor. Mean age was 63 years, 46% were women and 22% were African American. The median FGF‐23 level was 3098 RU/mL. Younger age, lower prevalence of diabetes, longer dialysis vintage, and higher calcium and phosphorus were independently associated with higher FGF‐23 levels. Higher FGF‐23 was independently associated with a lower memory score (per doubling of FGF‐23, β = −0.08 SD [95% confidence interval, CI: −0.16, −0.01]) and highest quartile vs. lowest quartile (β = −0.42 SD [−0.82, −0.02]). There was no definite association of FGF 23 with executive function when examined as a continuous variable (β = −0.03 SD [−0.10, 0.04]); however, there was a trend in the quartile analysis (β = −0.28 SD [−0.63, 0.07], P = 0.13, for 4th quartile vs. 1st quartile). FGF‐23 was associated with worse performance on a composite memory score, including after adjustment for measures of mineral metabolism. High FGF‐23 levels in hemodialysis patients may contribute to cognitive impairment.